Spy capitalism : Itek and the CIA - Lewis, Jonathan E., 1962- (Yale University Press, 2002)
What happens when the world of venture capital collides with the world of espionage? To find the answer, Jonathan Lewis takes us inside the executive suite at Itek Corporation during the Cold War years from 1957 to 1965. Itek was manufacturing the world's most sophisticated satellite reconnaissance cameras, and the information these cameras provided about Soviet missiles and military activity was critical to US security. So was Itek. This work examines in detail the challenges Itek faced not only as a contractor for the most important national security programme of the time - the CIA's Project CORONA spy satellite - but also as a start-up company competing with established industrial giants. In telling the story of Itek Corporation, Lewis seeks to fill important gaps in the history of American intelligence, business history and management studies. In addition, he addresses a variety of themes such as the compatibility of secrecy and capitalism, the struggle between profits and patriotism, and the workings of power and connections in America. Lewis explores how Itek executives contended with myriad business problems that were compounded by the need to raise capital without revealing the complete truth about the company's highly secret business. He also presents information about Laurance Rockefeller's venture capital operations and his role in financing Itek, based on the financier's private Itek papers. The volume is both a case study of a company at the heart of the American intelligence-industrial complex during the Cold War and an examination of the impact of the CIA on the capitalist system it was created to defend.